Recipes - Gerald Prince (Studies in 20th & 21st Century Literature, 1985)
After a distinction is made between avant-garde texts, post-modernist texts, and experimental texts, it is argued that the latter consist in the productions and products of recipes for textual rewritings. These rewritings must be systematic, bear on formal as opposed to contentual matters, and have as a dominant the exploration of writing rather than self or world. Furthermore, they may be more or less impersonal, explicit, massive, and new. To put it in other words, an experimental text is one that is taken to substitute the being of writing for the writing of being.
Keywords: avant-garde; post-modernism; post-modernist texts; avant-garde texts; textual rewriting; self; experimental text; being; writing